LC-MS/MS-Based Determination and Optimization of Linoleic Acid Oxides in Baijiu and Their Variation with Storage Time - Cheng Fang; Xiaotong Zhuang; Zhanguo Li; Yongfang Zou; Jizhou Pu; Dong Wang; Yan Xu (Metabolites)
Background: Post-production storage plays a pivotal role in developing the characteristic flavor profile of Baijiu, a traditional alcoholic beverage in China. While aging markers remain crucial for quality authentication, the identification of reliable metabolic indicators for chronological determination requires further exploration. Methods: This study establishes a novel liquid chromatography-tandem mass spectrometry (LC-MS/MS) methodology for quantifying five linoleic acid-derived oxidative metabolites in Baijiu: 9,12,13-trihydroxy-10(E)-octadecenoic acid (9,12,13-TriHOME), 9,10-Dihydroxy-12-octadecenoic acid (9,10-DiHOME), 9-oxo-(10E,12Z)-octadecadienoic acid (9-OxoODE), 9-hydroxy-(10E,12Z)-octadecadienoic acid (9-HODE) and 13-hydroxyoctadeca-(9Z,11E)-octadecadienoic acid (13-HODE). Results: The optimized protocol demonstrated exceptional sensitivity with limits of detection at 0.4 ppb through membrane-filtered direct dilution. Calibration curves exhibited excellent linearity (R2 > 0.9990) across 1.0–100.0 ppb ranges. Method validation revealed satisfactory recovery rates (87.25–119.44%) at three spiking levels (10/20/50 ppb) with precision below 6.96% RSD. Application to authentic samples showed distinct temporal accumulation patterns. Light-aroma Baijiu exhibited storage duration-dependent increases in all five oxides. Strong aroma variants demonstrated significant positive correlations for 9,12,13-TriHOME, 9,10-DiHOME, and 9-OxoODE with aging time. Conclusions: These findings systematically characterize linoleic acid oxidation products as potential aging markers, providing both methodological advancements and new insights into Baijiu aging mechanisms.